Kazakhstan's Multiple Energy Policy and Caspian Sea - Yerkinay ONGAROVA (Alınteri sosyal bilimler dergisi, 2018)
The most important thing in Kazakhstan's foreign policy is the development of energy routes, including the production and export of hydrocarbons. According to some estimates, with the availability of proven hydrocarbon reserves, Kazakhstan ranks 13th in the world. Its share of the world's proven reserves is: 3.2% in oil (about 5 billion dollars), 1.5% in gas (about 2 trillion cubic meters). The hydrocarbon factor plays an important role not only in Kazakhstan's economic development, but also in expanding its position in diplomatic and international spheres. Especially Kazakhstan has the largest share in the Caspian Sea, and according to other coastal states, it is at the forefront of the Caspian in terms of energy richness. This, on the other hand, makes Kazakhstan more important in the international arena in terms of geopolitics.